KOORDINASI KERJA FRONT OFFICE DEPARTMENT DENGAN HOUSEKEEPING DEPARTMENT DI ASTON KARIMUN HOTEL - Oktazana, Dian; Arief, Andi M. Rifiyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aims to determine about to find out Works Coordination of Front Office Department by Housekeeping Department at Aston Karimun HotelThis research to make use of qualitative method to analysis set of case, which to become the key informan in this research as much as six people’s. That is Front Office Manager, Executive Housekeeper, two people of Receptionist and Room Maid people’s. Sources were obtained through observation, interview and documentation.Based on result of this research, the conclusions of this research are work coordination between Front Office Department by Housekeeping Department still raising required.Keywords: Coordination, Front Office and Housekeeping.